ANALISIS SENTIMEN CALON PRESIDEN DAN WAKIL PRESIDEN PERIODE 2019-2024 PASCA DEBAT PILPRES DI TWITTER - Ardiansyah, Rizka (ScientiCO : Computer Science and Informatics Journal, 2019)
Social networking sites, such as Twitter and Facebook are one of the important spaces for political engagement. Twitter or Facebook have become common elements in political campaigns and elections, especially for Indonesia’s presidential election 2019. for the period 2019 - 2024 there are two presidential and vice presidential candidates namely Ir. H. Joko Widodo - Prof. Dr. K.H. Ma'ruf Amin and Lieutenant General (Ret.) H. Prabowo Subianto - H. Sandiaga Uno. B.B.A., M.B.A. the two candidates who ran for the election triggered a lot of related public opinion where the most suitable candidate to become the president of the next period. Public opinion is generally one of the determining factors for presidential candidates who will later win the election. Presidential candidate debate is the efforts of the election commission to facilitate the presidential candidates to introduce their work programs to the public while building public opinion that they are the right people to become leaders of the next period. Although of course, this is not the only major factor that shapes public opinion. The purpose of this study is to summarize the opinions of the people voiced through social media related to the election of candidates for the Indonesian President and Vice President for the period 2019-2024 post debate on the presidential election. While the benefit is to help the community so that they can understand in a broader context such as what the public opinion about presidential candidates, especially on social media Twitter. The results of this study were presidential candidate Joko Widodo - Makruf Amin obtained a 25% positive sentiment, 4.5% negative sentiment and 70.5% neutral sentiment. while the Prabowo Subianto - Sandiaga Uno pair received a 5.1% positive sentiment, 2.5% negative sentiment and 92.4% neutral sentiment.